(Post-)deuteronomistyczny zakaz transwestytyzmu (Pwt 22,5)? Pytanie o jego właściwy sens i motywację - Lemański, Janusz (Collectanea Theologica, 2020)
Deut 22:5 is the only prohibition of transvestitism in the Bible and its cultural environment. The context in which it appears suggests that it was inserted secondarily, in the period after the Babylonian Exile. This view narrows down various speculations concerning the original Sitz im Leben of this precept, and it leads one to understand it primarily within the framework of the canonical shape of the whole Pentateuch. Accordingly, this regulation mainly refers to the rule of the bisexual division of human nature (Gen 1–2), the rule of preserving the order of creation (not mixing species; Lev 19:19; Deut 22:9-11), as well as the preservation of the procreative force, here mainly related to masculinity (Gen 5:1-3; cf. 1:28; 9:1.7).